Climate records from different places in black cherry - pine forests in the Havelland, north-eastern Germany - Jonas Geschke (PANGAEA, 2018)
The data has been gathered in order to investigate the influence of the invasive black cherry (Prunus serotina Ehrh.) on bats (Chiroptera: Verpertilionidae) in Scots pine (Pinus sylvestris) forest ecosystems. The bat calls were recorded using automated recording devices (batcorders) in pine forest stands with three different black cherry densities (pine monoculture, light and dense black cherry) for a period of 60 survey nights between the end of July and late September 2016. Three plots per forest type were sampled with a repetition of 20 survey nights per plot. A total of 3888 bat call recordings were made during the study period, from which eight bat species could be identified to species level. Additionally to the bat calls, climate data (temperature and humidity) was collected with the same sampling design as the bat call recording.